Report of the 1984 conjugate campaign in Iceland - Natsuo Sato; Ryoichi Fujii; Susumu Kokubun; Takashi Araki; Th. Saemundsson (National Institute of Polar Research, 1985)
This campaign has been organized by the National Institute of Polar Research as a cooperative project with the Science Institute, University of Iceland. This campaign aims at a further understanding of physical processes in auroras by a coordinated observation of magnetic field variations, magnetic ULF waves, ELF-VLF emissions, cosmic noise absorption, and spatial and temporal variations of auroras in the geomagnetically conjugate polar regions. With the data recorded at the three conjugate station pairs Syowa-Husafell, Mizuho-Isafjordur, and Molodezhnaya-Tjornes, we investigate the temporal and spatial conjugacy of both auroras and wave phenomena associated with auroral particle precipitation. Then we study the auroral particle acceleration process in the ionosphere-magnetosphere energy coupling system and also the generation and propagation mechanisms of ULF, ELF and VLF plasma waves. Four Japanese scientists have been in Iceland from August 13 to October 7,1984. Fluxgate magnetometer, search coil magnetometer, riometer, ELF/VLF wave receiver, photometer, and analogue and digital data recorders were set up at Isafjordur (66.1°N, 23.1°W) and Tjornes (66.2°N, 17.1°W) in August 1984. Simultaneous observations at three stations in Iceland including Husafell (64.7°N, 21.0°W), where most of instruments had been constructed in 1983,started from September 2,1984 corresponding to the conjugate observations in Antarctica. During their stay in Iceland, visible auroral data have been obtained simultaneously at conjugate-pair stations at four nights.